“THE FLICKER OF SENSES” IN TEXT CREATION PROCESSES - Kononenko, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the phenomenon of Reassessment of words and phrases in processes of text – and image-creation. Semantic changes cause language-aesthetic effect, become the foundation of metaphorization, symbolism, personification, affect the figurative structure of discourse. Sense expansion is accompanied with changes in associative-valuation area, usage of allusion, antinomy, comparison and other means.